Insights Into the Microbiology of the Chaotropic Brines of Salar de Atacama, Chile - Cubillos, Carolina F.; Paredes, Adrián; Yáñez, Carolina; Palma, Jenifer; Severino, Esteban; Vejar, Drina; Grágeda, Mario; Dorador, Cristina (Frontiers in Microbiology, 2019)
Microbial life inhabiting hypersaline environments belong to a limited group of extremophile or extremotolerant taxa. Natural or artificial hypersaline environments are not limited to high concentrations of NaCl, and under such conditions, specific adaptation mechanisms are necessary to permit microbial survival and growth. Argentina, Bolivia and Chile include three large salars (salt flats) which are represent the largest lithium reserves globally, and that are commonly referred to as the Lithium Triangle zone. To date, a large amount of information has been generated regarding chemical, geological, meteorological and economical perspectives of these salars. However, there is a remarkable lack of information regarding the biology of these unique environments. Here we report the presence of two bacterial strains from one of most hypersaline lithium-dominated man-made environments (55.6%) reported to date. Both isolates were classified to the Bacillus genera, but displayed differences in 16S rRNA gene and fatty acid profiles. Our results also revealed that isolates are lithium-tolerant and that they are phylogenetically differentiated to Bacillus associated with high NaCl concentration environments, and form a new clade from the “Lithium Triangle” zone. To determine osmoadaptation strategies in these microorganisms, both isolates were characterized using morphological, metabolic and physiological attributes. We suggest that our characterization of bacterial isolates from an environment highly enriched in lithium has revealed that even at such extreme salinities, scope for microbial life exists. These conditions have previously been considered such as to limit the development of life, and extends the window of life beyond high concentrations of MgCl2, as previously reported, to LiCl. Our results will support the future understanding of resistance mechanisms to saline stress beyond NaCl, and likely have value as study models for the understanding of putative extra-terrestrial (e.g. Martian) life.